Pengaruh Store Atmosphere dan Keragaman Produk terhadap Keputusan Pembelian Konsumen pada Butik Faris Fashion Karawang - Riska Hoeratunisa; Odang Kusmayadi (Universitas Batanghari, 2022)
The purpose of this study was to determine the relationship between Store Atmosphere and Product Diversity, to determine the partial effect of Store Atmosphere and Product Diversity on Purchase Decisions, to determine the simultaneous effect of Store Atmosphere and Product Diversity on Purchase Decisions. The method used in this research is to use descriptive and verification with a quantitative research approach. The sample used in this study was 317 samples using the incidental sampling technique. Withdrawal of respondents as a sample based on chance. The data analysis technique used is path analysis with partial and simultaneous hypothesis testing. The results of this study are that there is a fairly strong positive and significant relationship between the store atmosphere variable and product diversity, which is 0.537. There is a partial effect of Store Atmosphere and Product Diversity on Purchase Decisions showing that the magnitude of the associative positive degree or path coefficient of the Store atmosphere variable (X1) is 0.414, smaller than the Product Diversity variable (X2) 0.436, meaning that product diversity (X2) has a greater contribution to the decision. purchases (Y) versus Store atmosphere (X1). Simultaneous effect caused by Simultaneous Store atmosphere (X1) and product diversity (X2) influence on purchasing decisions (Y)